Review on the elaboration and characterization of ceramics refractories based on magnesite and dolomite. Issue 3 (1st September 2016) - Sadik, Chaouki; Moudden, Omar; El Bouari, Abdselam; El Amrani, Iz-Eddine
Abstract: One of the most important elements of furnaces, boilers and other heating units is the structure (lining), usually made of silica–alumina, basic or special refractories. The basic refractories are materials that are increasingly in demand and whose manufacturing involves necessarily the use of MgO and CaO. In this article, the description and characterization of magnesite (MgCO3 ) and dolomite (Mg, Ca(CO3 )2 ) and their contribution in industrial ceramics-refractories have been reviewed.